2016
DOI: 10.1542/peds.2015-2469
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Exome Sequencing Study of Language Disorder in an Isolated Population

Abstract: BACKGROUND AND OBJECTIVE: Developmental language disorder (DLD) is a highly prevalent neurodevelopmental disorder associated with negative outcomes in different domains; the etiology of DLD is unknown. To investigate the genetic underpinnings of DLD, we performed genome-wide association and whole exome sequencing studies in a geographically isolated population with a substantially elevated prevalence of the disorder (ie, the AZ sample).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Our laboratory has recently conducted a behavioral association and neuroimaging genetic study of the SETBP1 gene, which was previously associated with expressive language function in an isolated population in Russia with a high prevalence of DLD (Kornilov et al, ). This population is of interest for investigating a shared genetic cause of DLD because its remote location leads to reduced genetic diversity and increased heritability of traits within the population.…”
Section: Additional Genes Linked To Reading and Languagementioning
confidence: 99%
“…Our laboratory has recently conducted a behavioral association and neuroimaging genetic study of the SETBP1 gene, which was previously associated with expressive language function in an isolated population in Russia with a high prevalence of DLD (Kornilov et al, ). This population is of interest for investigating a shared genetic cause of DLD because its remote location leads to reduced genetic diversity and increased heritability of traits within the population.…”
Section: Additional Genes Linked To Reading and Languagementioning
confidence: 99%
“…One strategy is to apply whole-exome or wholegenome sequencing in large families showing potential monogenic transmission of a languagerelated disorder [93,94], although there are no guarantees that such approaches will pinpoint a single causal variant in the family being studied. [ 4 2 5 _ T D $ D I F F ] Useful insights may also emerge from GWAS and/or NGS in geographical isolates with dramatically increased prevalence of language disorders, as shown by studies of SLI implicating variants in SETBP1 and MEF2-regulated genes in a remote cluster of Russian villages [95], and a variant of NFXL1 in a founder population from Robinson Crusoe Island (Chile) [96]. Another means for identifying high-penetrance variants is to sequence entire exomes/genomes of parent-child trios, in which there is a proband with a severe sporadic disorder.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Our previous genome‐wide association study of DLD in AZ revealed several novel candidate genes (Kornilov et al., 2016), including SETBP1 , which demonstrated a statistically significant gene‐level association with the quantitative trait “syntactic complexity” (a phenotype derived from a combination of syntactic indices we obtained from language samples of the participants) after corrections for multiple comparisons. SETBP1 provides instructions for making the protein called SET binding protein 1, which functions as a regulator of gene activity.…”
Section: Introductionmentioning
confidence: 96%
“…Despite its high prevalence (5–10%; Law, Boyle, Harris, Harkness, & Nye, 2000; Tomblin et al., 1997), DLD remains one of the most understudied neurodevelopmental disorders with regard to its neurobiological (i.e., molecular‐genetic, neuro‐anatomical, and neuro‐functional) etiology (Bishop, 2017). Recently, a number of whole‐genome association studies of language‐related traits and DLD have been published (e.g., Chen et al., 2017; Devanna et al., 2018; Eicher et al., 2013; Gialluisi et al., 2014; Harlaar et al., 2014; Kalnak et al., 2018; Kornilov et al., 2016; Laffin et al., 2012; Luciano et al., 2013; Nudel et al., 2014; Simpson et al., 2015; St. Pourcain et al., 2014). As reviewed in detail elsewhere (e.g., Deriziotis & Fisher, 2017; Reader, Covill, Nudel, & Newbury, 2014), these studies identified a number of tentative genetic associations with small effect sizes implicating a complex network of genes in the development of language and language‐related traits and disorders; however, the majority of reported associations did not survive stringent statistical corrections for multiple comparisons.…”
Section: Introductionmentioning
confidence: 99%